Vulnerabilidade ambiental ao óleo em ambiente fluvial: estudo de caso rio Tietê/Reservatório de Barra Bonita - Beneditti, Cristina Aparecida [UNESP] (2015)
Accidents involving oil spills are extremely worrying, as they cause severe damage to the environment, whether water or land, impacting the fauna, flora and also the population directly or indirectly depends on natural resources. But only in the 80s, after serious accident in Alaska is that it was established more stringent measures for transportation, oil storage and response plans to accidents. However, larger magnitude of events involving large volumes and poured occurs in the coastal area and therefore, for this environment, already have rules and methodology of analysis of the sensitivity and environmental vulnerability to further consolidated oil. Not so for the riverine environment. But there is a forecast increase of vessels in the waterways of Brazil carrying grain, sugar and ethanol, which increases the possibility of accidents with diesel oil spill, either directly train as the supply points. In case this kind of accident occurs, it is important to know which is the oil course on the riverdyke, as well as when and in which magnitude it will reach environmentally sensitivity areas. Thus, the main aim of this thesis was to elaborate a vulnerability environmental scenery to oil in fluvial environment, more specifically on the river Tietê stretch and reservoir of Barra Bonita in São Paulo state. For both, a mapping of the fluvial sensitive environmental index to oil (ISF) to the study areas was carried out, considering the geomorphology of the river. Also was carried out a simulation of an accident in an inter-modal harbor, located in Anhembi, which have considered typical characteristics of wind and rainfall to the flood (May) and ebb (November) period in there reservoir. Using the software SisBaHiA, were elaborated scenery to 12h, 36h, 60h e 72h after the overflow have started, to follow the displacement of the spot contamination. The simulation results were divided in three classes, according to the oil permanency time: no ...